Raza, nación, olvidos y falacias históricas: análisis de libros de texto de español en Estados Unidos. - BAPTISTA, GONZALO (Revista de Estudios Hispánicos, 2023)
A decolonial analysis of teaching materials provides insight into the ways in which Spanish culture, history, and society are conveyed in the language curriculum in the United States. Focusing on textbooks adopted for the course "Culture and Civilization", this article evaluates the identities which are privileged in the discourse, and the ones that are discriminated. Non-white ethnic or racial groups are subcategorized through negative stereotypes. This marginalization -- or even exclusion--invites us to consider the degree of racism distilled in such manuals. First, after reviewing decolonial perspectives in education, this article assesses the degrading bias applied to the Roma community. Second, it analyzes two historical lacunae: the planned genocide against them and the presence of enslaved Black people. These absences privilege a cultural identity narrative focused on white men since the so-called Reconquista. Third, this article reviews an uncritically reiterated historical fallacy: the loss of the Spanish colonies in 1898. In this sense, the article summons the incidence of Spanish colonialism in Africa to be included in textbooks. Finally, it evaluates approaches to promote an active decolonization, without resorting to diversity as a mere agglutinating ornament.